Pola Komunikasi Kelompok Gamers Perempuan pada Game Online - Chen, Danial; Paramita, Sinta (Kiwari, 2024)
This research analyzes communication patterns between members of a group of female game rs in the online game Mobile Legends. Then explores social factors, such as friendship or interpersonal relationships, which influence communication patterns during the game. In the context of communication patterns of female groups in the online game Mobile Legends, there are several aspects which can be analyzed to understand the communication dynamics that occur. Groups of women in this game often show different communication characteristics, which involve coordination, strategy, and unique social interactions. Group communication is communication that takes place between a communicator and a group of more than two people. If the number of people in the group is small, which means the group is small, the communication that takes place is called small group communication. However, if the number is large, it means the group is called large group communication. The aim of this research is to examine communication patterns of women's groups in the Mobile Legends game. This research uses a case study method with a qualitative approach based on group communication theory. The results of this research were carried out in four parts, from the four parts the group communication patterns in women were explained in more detail. Penelitian ini menganalisis pola komunikasi antaranggota kelompok gamers perempuan dalam game online Mobile Legends. Lalu mengeksplorasi faktor-faktor sosial, seperti persahabatan atau hubungan interpersonal, yang mempengaruhi pola komunikasi selama pertandingan. Dalam konteks pola komunikasi kelompok perempuan pada game online Mobile Legends, terdapat beberapa aspek yang dapat dianalisis untuk memahami dinamika komunikasi yang terjadi. Kelompok perempuan dalam permainan ini seringkali menunjukkan karakteristik komunikasi yang berbeda, yang melibatkan koordinasi, strategi, dan interaksi sosial yang unik. Komunikasi kelompok adalah komunikasi yang berlangsung antara seorang komunikator dengan sekelompok orang yang jumlahnya lebih dari dua orang. Apabila jumlah orang dalam kelompok itu sedikit yang berarti kelompok itu kecil, komunikasi yang berlangsung disebut komunikasi kelompok kecil. Namun apabila jumlahnya banyak berarti kelompoknya dinamakan komunikasi kelompok besar. Tujuannya dari penelitian ini yaitu untuk meneliti pola komunikasi kelompok perempuan dalam game Mobile Legends. Penelitian ini menggunakan metode studi kasus dengan pendekatan kualitatif dengan didasari teori komunikasi kelompok. Hasil penelitian ini dilalui oleh empat bagian, dari ke empat bagian tersebut lebih di jelaskan secara detail tentang pola komunikasi kelompok pada perempuan.